2020
DOI: 10.1097/md.0000000000018573
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant melanoma of the esophagus with multiple lymph node metastases

Abstract: Rationale: Primary malignant melanoma of the esophagus (PMME) is a very rare malignancy accounting for only 0.1% to 0.2% of all malignant esophageal lesions. Presently, there are no standard strategies or clear guidelines for PMME treatment. Patient concerns: Herein, we report a patient who had PMME with multiple lymph node metastases (LNMs) who was treated successfully by esophagectomy. In March 2018, a 74-year-old man with symptoms of continuous dysph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Esophageal melanoma typically affects older people in the 6 th or 7 th decade of life with a maleto-female ratio of 2-3:1 [1]. About 90% of cases involve the middle or lower third of the oesophagus and typically present as dysphagia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esophageal melanoma typically affects older people in the 6 th or 7 th decade of life with a maleto-female ratio of 2-3:1 [1]. About 90% of cases involve the middle or lower third of the oesophagus and typically present as dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Primary malignant melanoma is an exceedingly rare neoplasm accounting for about 0.1% to 0.2% of all malignant esophageal neoplasms [1]. It is mostly reported in elderly males, typically present as dysphagia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these authors renewed the need to employ techniques such as massive gene sequencing to be able to search for biomarkers capable of predicting the response of PMME to anti-PD1 immunocheckpoint inhibitors. After another 38 cases of PMME [ 274 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 ], Endo F. et al [ 290 ] reported a case of a 70-year-old man who complained of dysphagia due to the presence of a polypoid lesion in the lower thoracic esophagus. Although the histopathological examination had provided the diagnosis of esophageal squamous carcinoma at first, with subsequent pT3N1M0 staging and clinical stage III, a histological re-evaluation after radical esophagectomy revealed the presence of atypical melanocyte cells positive for S-100 protein, Melan-A and HMB-45, and, therefore, PMME was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…About 18.4% of PMME patients present with metastatic disease at the time of diagnosis and 89.7% develop recurrence or metastasis within a few months from diagnosis [1] . As a result, PMME tends to have a poor 5-year overall survival (OS) ranging between 4% to 37.5% [1] , [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%